2018
DOI: 10.1111/epi.14526
|View full text |Cite
|
Sign up to set email alerts
|

The specificity and role of microglia in epileptogenesis in mouse models of tuberous sclerosis complex

Abstract: Microglia abnormalities may contribute to epileptogenesis in the context of neuronal involvement in TSC mouse models, but selective Tsc1 gene inactivation in microglia alone may not be sufficient to cause epilepsy, suggesting that microglia have more supportive roles in the pathogenesis of seizures in TSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…Therefore, they concluded that the effects seen in Tsc1 CX3CR1 mice were not exclusively driven by reactive microglia but could also be elicited by affected neurons and astrocytes. Furthermore, post-natal induction of the knockout, which had a higher specificity for microglia showing only 5% of non-microglial cells affected, did not result in spontaneous ictal activity (218), in contrast to the previous study (217). These studies emphasize that it is essential to precisely target and characterize cell types in TSC KO models, as only small percentages of affected neurons can lead to increased neuronal excitability (219).…”
Section: Microgliamentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, they concluded that the effects seen in Tsc1 CX3CR1 mice were not exclusively driven by reactive microglia but could also be elicited by affected neurons and astrocytes. Furthermore, post-natal induction of the knockout, which had a higher specificity for microglia showing only 5% of non-microglial cells affected, did not result in spontaneous ictal activity (218), in contrast to the previous study (217). These studies emphasize that it is essential to precisely target and characterize cell types in TSC KO models, as only small percentages of affected neurons can lead to increased neuronal excitability (219).…”
Section: Microgliamentioning
confidence: 78%
“…All of the Tsc1 CX3CR1 mice developed spontaneous recurrent seizures around 5 weeks of age, as well as two-thirds of the post-natally induced conditional knockout mice. However, that same year, Zhang et al (218) reported that CX3CR1-Cre driver lines in Tsc1 CX3CR1 animals target not solely the alleged microglia cells, but also NeuN-and rarely GFAP-positive cells. Therefore, they concluded that the effects seen in Tsc1 CX3CR1 mice were not exclusively driven by reactive microglia but could also be elicited by affected neurons and astrocytes.…”
Section: Microgliamentioning
confidence: 99%
“…To date, different CX3CR1-Cre lines have been developed and widely used in a number of studies, focusing on the roles of microglia in the CNS (Parkhurst et al, 2013;Peng et al, 2016). However, it is also reported that some CX3CR1-Cre lines have a possibility for leakage of Cre expression into other cells, such as neurons and astrocytes (Hwang et al, 2017;Zhang et al, 2018). Zhao et al was neither observed in neurons nor in astrocytes in CX3CR1-Cre mice obtained from MMRRC (#036395) and concluded that the line was microglia-specific (Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies in TSC mouse models point to a possible role for microglia abnormalities (resulting from Tsc1 inactivation) in contributing to epileptogenesis; however, whether microglial cells are primary contributors to epilepsy and associated comorbidities is still matter of discussion (Zhang et al. ; Zhao et al. ).…”
Section: What We Have Learned So Farmentioning
confidence: 99%